Biological effect of protein modifications by lipid peroxidation products. (July 2019) - Gęgotek, Agnieszka; Skrzydlewska, Elżbieta
Highlights: Lipid peroxidation products – protein adducts are responsible for cellular signaling regarding various metabolic pathways. 4-HNE-protein adducts formation supports antioxidant response through changes in the transcriptional activity. MDA-protein adducts stimulates pro-inflammatory signaling. Acrolein-protein adducts promote apoptosis. Protein adducts with products of PUFAs cyclisation lead mainly to inflammation or apoptosis. Abstract: The products of lipid peroxidation, resulting from cell metabolism as well as the action of external physical factors and xenobiotics, have a significant impact on cell functions. One of the mechanisms by which lipid peroxidation products influence cells is the formation of adducts with proteins, including enzymes and signaling molecules. This review describes the biological consequences of protein adduct formation with oxidative lipid fragmentation products such as 4-hydroxynonenal (4-HNE), malondialdehyde (MDA), and acrolein, as well as cyclization products including isoprostanes, isoketals, and isolevuglandins. The generation of protein adducts with lipid peroxidation products can stimulate the antioxidant system, which may also possess proinflammatory or proapoptotic effects. However, the role of adducts between lipid peroxidation products and proteins depends on the condition of the cells and can range from the function of cytoprotective activity stimulation, to induction of toxicity involved in the development of degenerative diseases.